Results from the AUSTRAL Geodetic VLBI Network - Liu, Jia (Auckland University of Technology, 2016)
Very Long Baseline Interferometry (VLBI) is a space geodesy technique used to determine the Celestial Reference Frame (CRF); it contributes to the definition of the Terrestrial Reference Frame (TRF) and it is the only space geodetic technique that provides the full set of Earth Orientation Parameters (EOPs), which are important for positioning and navigation on Earth and in space. Contribution of the southern hemisphere geodetic VLBI stations in the International VLBI Service for Geodesy and Astrometry (IVS) expanded significantly since the AUSTRAL VLBI program was started in 2011. The AUSTRAL geodetic VLBI network consists of five radio telescopes: WARK12M in New Zealand, three AuScope 12-m antennas (Hobart, Katherine and Yarragadee) in Australia, and HART15M in South Africa. There are theoretical models which determine coordinates and velocities of AUSTRAL stations. However, one can expect that their accuracy is not high, because they are based on limited and sparse time series of first years of AUSTRAL observations (2012–2013 for VieTrf13 and 2012–2014 for ITRF2014-IVS). Here, I include two more years of observations (up to mid-2016) to test quality of the theoretical models of the AUSTRAL stations. The latest version Vienna VLBI Software VieVS (version 2.3) is used to process and analyse geodetic VLBI observational data from the global (IVS-R1/R4) and the regional (AUSTRAL) sessions for the period from 2012 to the mid of 2016. I find that there is discrepancy between Global Navigation Satellite Systems (GNSS) and VLBI results. In some cases, there is indication that VLBI models need improvement. I compute the horizontal coordinates (NEU). I find that horizontal (North and East) components are more stable (smaller errors) than the vertical (Up) component. I find that the WARK12M VLBI Up-residual shows vertical motion about −2 cm/yr. The co-located GNSS does not show noticeable motion – much less than 1 cm/yr. The local tie survey for the same period did not show distance change between GNSS and radio telescope. I conclude that the a priori model needs adjustment. In some cases, more obervations with the Warkworth 12-m radio telescope are required. I calculate the velocities of VLBI and GNSS stations, and the baseline rates of change for both of VLBI and GNSS stations of the AUSTRAL array. I found that the ITRF2014 describes baseline rates of change is better than the VieTrf13. In some cases discrepancies between models and observations are significant. I conclude that the models of our AUSTRAL stations need to be adjusted. It is the troposphere that is one of the most important error sources for space geodetic techniques which rely on radio signals (VLBI and GNSS). To achieve accuracy of telescope coordinate determination at the millimetre level, an accurate troposphere delay modelling is needed. I investigate the tropospheric zenith wet delay (ZWD) for the AUSTRAL stations. I discuss the seasonal variations (signals) of the ZWD. I compare the ZWD results obtained from VLBI with the ZWD results based on the GNSS measurements for the Warkworth Global Geodetic Observing System (GGOS) station. I find that the geodetic results for VLBI and GNSS present a good agreement. I conclude that the AUSTRAL sessions are suitable to measure ZWD. I consider VLBI sessions which involve AUSTRAL stations only and sessions that include AUSTRAL station and other IVS stations. I compute and compare the EOPs and demonstrate that the more stations are involved and the more regular is the distribution of IVS stations on the globe, the higher the accuracy of EOPs determined in these sessions.
Keywords: Very Long Baseline Interferometry; VLBI Network; Space Research; Radio Astronomy